2020
DOI: 10.7759/cureus.9735
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antimicrobial Resistance in Agents Causing Urinary Tract Infections at a Tertiary Care Hospital in a Developing Country

Abstract: Background and objective Urinary tract infections (UTIs) are usually treated with empirical therapy by physicians based on previous knowledge of the predictability of causative agents and their antimicrobial susceptibilities. The objective of this study was to determine the frequency of various pathogens causing UTIs and their antimicrobial resistance profile in patients presenting to the outpatient department (OPD) of a tertiary care hospital. Materials and methods This descriptive cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The susceptibility of E. coli strains to ampicillin has been reported to range from 11.6% to 28% [12,15], and its susceptibility to fosfomycin ranged from 60% to 98% [7,13,16]. On the other hand, the sensitivity to nitrofurantoin was found to be high in many studies (86.45%-94%) but low (59%) in the study of Kidwai et al [1,7,8,13,15,16].…”
Section: Discussionmentioning
confidence: 96%
“…The susceptibility of E. coli strains to ampicillin has been reported to range from 11.6% to 28% [12,15], and its susceptibility to fosfomycin ranged from 60% to 98% [7,13,16]. On the other hand, the sensitivity to nitrofurantoin was found to be high in many studies (86.45%-94%) but low (59%) in the study of Kidwai et al [1,7,8,13,15,16].…”
Section: Discussionmentioning
confidence: 96%
“…The emerging strategies of using alternative therapies like probiotics and maintenance of hygiene have also helped in preventing resistance [18]. The most important of all the preventive measures is the rational and specific use of antibiotics according to the laboratory reports and prescriptions [20,21]. A single-centered cross-sectional study design and convenience sampling technique are few limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Various urine culture studies in Pakistan have reported E. coli as the most common uropathogen ranging from 52%-77.4 % [24][25][26][27][28][29]. Another common organism was Klebsiella pneumoniae ranging from 1.9%-18.69% [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Various urine culture studies in Pakistan have reported E. coli as the most common uropathogen ranging from 52%-77.4 % [24][25][26][27][28][29]. Another common organism was Klebsiella pneumoniae ranging from 1.9%-18.69% [24][25][26][27][28][29]. Few of the other uropathogens reported were Pseudomonas aeruginosa, Enterobacter, and Proteus mirabilis [24][25][26][27][28][29] After the discovery of penicillin, antibiotics have revolutionized healthcare.…”
Section: Discussionmentioning
confidence: 99%